Rats or garbage? Dehumanizing politicians through metaphor - Novi Eka Susilowati; I Dewa Putu Wijana; Hayatul Cholsy (Studies in English Language and Education, 2026)
The public often show their disappointment with dishonest politicians through dehumanizing metaphors. This study aimed to analyze the use of metaphors to dehumanize Indonesian politicians on X social media, formerly Twitter. The data of this study were collected from the comment columns of X accounts owned by mainstream Indonesian news agencies, consisting of @CNNIndonesia, @kompas.com, @KompasTv, @tvOneNews, and @detikcom. We collected 3.710 comments containing 106 dehumanization metaphors. The study results show that dehumanization metaphors towards politicians consisted of animal domain metaphors (anthropomorphic) and object domain metaphors that are specifically in the form of garbage (objectification). Metaphor producers ignored human characteristics, thus creating dehumanizing metaphors. Dehumanizing metaphors are carried out by (1) animalizing or objectifying politicians based on their behavior and appearance, (2) associating politicians’ emotions with animals or garbage, and (3) associating politicians’ characteristics with types of animals or garbage. Dehumanization metaphors were used in public discourse to express anger toward politicians, reflecting perceptions that campaign promises were unfulfilled or that politicians’ behavior was objectionable. The results of this study indicated that the public employs specific strategies to criticize politicians, often through dehumanizing metaphors that intensify hatred or indifference and may contribute to discrimination or violence. Indonesian political discourse, frequently dominated by loosely moderated buzzer accounts, provides many such instances. These metaphors demonstrate how language functions as a powerful framing tool that shapes public perceptions, reduces trust in politicians, and increases political polarization.